2010
DOI: 10.2108/zsj.27.762
|View full text |Cite
|
Sign up to set email alerts
|

A New In Vitro Ovulation Model for Medaka Based on Whole Ovary Culture

Abstract: We sought to establish a new in vitro ovulation model using the whole ovaries of the medaka. Ovaries of the fish, which had been acclimated to the usual reproductive conditions (26°C, 14 h light/10 h dark) and which had then been kept at least one day at 30°C, were isolated 2 h before the expected in vivo ovulation time. When the ovaries were cultured in 90% medium 199 solution at 30°C or 36°C, oocytes were liberated with a gradual increase in the ovulation rate at 2 to 5 h of ovulation time. The maximum ovula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The viability of follicles at the end of each culture period was evaluated by staining with 0.08% trypan blue. In vitro fertilization was performed as previously described [14]. The developmental stage of the embryos was determined as previously described [73].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viability of follicles at the end of each culture period was evaluated by staining with 0.08% trypan blue. In vitro fertilization was performed as previously described [14]. The developmental stage of the embryos was determined as previously described [73].…”
Section: Methodsmentioning
confidence: 99%
“…(ii) The timing of the sequential processes of spawning, such as completion of vitellogenesis, breakdown of the germinal vesicle and ovulation, can be determined. (iii) Experimental systems for studying ovulation with whole ovaries and dissected follicles in vitro are available [14]–[16]. (iv) The proteolytic enzymes responsible for follicle rupture in ovulation have been determined [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, molecular details of oocyte liberation from ovarian follicles and release into the oviduct, as well as coordination of these processes with oocyte maturation, have not been well studied. Some in vitro ovulation models have been developed in mammals and the medaka fish Oryzias latipes . In frogs, in vitro maturation and ovulation of Rana pipens and Rana dybowskii oocytes was observed in the ovarian fragments and isolated follicles treated with pituitary extracts.…”
Section: Ovulation and Maturationmentioning
confidence: 99%
“…Some in vitro ovulation models have been developed in mammals [16][17][18] and the medaka fish Oryzias latipes. [19][20][21] In frogs, in vitro maturation and ovulation of Rana pipens and Rana dybowskii oocytes was observed in the ovarian fragments and isolated follicles treated with pituitary extracts. In these studies, however, the experimental treatments failed to induce follicular rapture.…”
Section: Ov Ul Ati On and Matur Ati Onmentioning
confidence: 99%
“…In addition, in vitro ovulation models developed for the medaka fish Oryzias latipes allowed identification of the hydrolytic enzymes responsible for oocyte liberation during medaka ovulation. It was demonstrated that the follicle rupture during ovulation involves cooperation of the MMP tissue inhibitor with at least three different MMPs [23,24,25]. In frogs, in vitro maturation and ovulation of Rana pipiens and Rana dybowskii oocytes was observed in the ovarian fragments and isolated follicles treated with homologous pituitary extracts [26,27,28].…”
Section: Introductionmentioning
confidence: 99%